Avaliações em larga escala: macro e microrregulações na escola - Lucchesi, Maria Eliéte Lacerda (Universidade Federal de São Carlos, 2023)
Periodically, basic education has been evaluated in the country in a census by Prova Brasil, a large-scale evaluation that represents a new regulation form by the State, which increasingly assumes the evaluator role. The new regulation modes, especially large-scale assessment, have a great impact on educational systems, especially on schools, configuring themselves as macroregulation. Within the school institution, there are teachers and other actors, such as school administrators, who, in the face of large-scale evaluation, adjust regulations in effective work with students, producing, in this process, microregulations. This research investigated how the microregulations exercised by teachers and administrators occur in the face of the large-scale evaluation process in a school unit of municipal basic education, in the period from 2011 to 2019 - years of application of the Prova Brasil and edition of the IDEB. The general objective was to analyze, in view of the large-scale assessment called Prova Brasil, the microregulations present within the referred school unit. And as specific objectives, to identify in which actions of school administrators and some teachers they are present, to understand how they occur and in which areas of activities and, finally, what are their motives and their own logic. Using a qualitative approach, data were obtained for this study through semi-structured interviews with teachers and administrators and a focal group with teachers. The results revealed that the teachers and administrators act in several domains of action with different interests, however using similar strategies that over the years constituted the logic of action of the school, some of these logics recovered from the performance in the face of other regulations on the school routine, others constituted specifically for the Prova Brasil. The logics of action are strengthened mainly in the field of school culture, where resistance or conformation to the policy is also defined. The personal interests of teachers and managers overlap with other interests, even ideological ones, especially when it comes to the school's reputation and performance standards, elements capable of redefining institutional priorities. The internal regulation exercised by the leadership style and the exercise of power by the school management greatly alleviated the conflicts, transforming, over the period, the initial resistance into conformation, especially in the face of a policy of continuity such as large-scale evaluation. Finally, we identified that the logics of action guide conduct at school and the microregulations exercised by teachers and administrators move in alternation and overlap related to the concern with student learning and the school's reputation in the IDEB ranking, but they cannot be underestimated by creators and formulators of public policies in the field of education, because, in the translation of policies into practice, in microregulations at school, the interests of the actors remain in the foreground, overlapping the very objectives of the policies.
Large-scale assessments: macro and microregulations at school
Keywords: Educação; Macrorregulação; Microrregulações; Avaliação em larga escala; Education; Macroregulation; Microregulations; Large-scale assessment; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::PLANEJAMENTO E AVALIACAO EDUCACIONAL; CIENCIAS HUMANAS::EDUCACAO::PLANEJAMENTO E AVALIACAO EDUCACIONAL::POLITICA EDUCACIONAL